A kind of blast furnace carbon grouting material and preparation method thereof

By using specific raw materials and additives in the blast furnace grouting material, the formation of magnesium aluminum spinel and CR2ALC triple ceramic structure solves the problem of decreased intensity after the fluidity of the grouting material in the existing technology, and the intensity at high temperature increases the intensity of intensity Keep liquidity.

CN118930276BActive Publication Date: 2025-01-28BEIJING LIRR HIGH-TEMPERATURE MATERIALS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411427503.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-14
Publication Date
2025-01-28
Estimated Expiration
2044-10-14

AI Technical Summary

Technical Problem

After the existing blast furnace grouting material increases fluidity, its strength decreases, making it difficult to effectively seal the furnace cylinder cracks at high temperatures.

Method used

Use silicon carbide particles, petroleum coke particles, alum soil particles, silicon carbide fine powder, coke powder, alum soil powder, electric magnesium powder, silicon powder, quartz powder, metal aluminum powder, metal chromium powder and other raw materials, and add liquid Resin, through the combination of particles and micro powder and the addition of metal powder, forms magnesium aluminum spinel and CR2ALC triple -like ceramic structure to improve high temperature intensity.

Benefits of technology

It has achieved excellent strength performance at high temperatures at high temperatures, while maintaining good liquidity at the same time, which can effectively block the furnace cracks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention provides a blast furnace carbon grouting material and a preparation method thereof. The raw materials for preparing the blast furnace carbon grouting material include the following components in mass percentage: 10% to 35% silicon carbide particles, 10% to 32% petroleum coke particles, 1% to 5% alumina particles, 30% to 45% silicon carbide fine powder, 1% to 8% coke powder, 1% to 4% alumina powder, 1% to 5% fused magnesia powder, 1% to 4% silicon powder, 2% to 6% quartz powder, 0.05% to 1% metal aluminum powder, 0.05% to 1% metal chromium powder, and 20% to 30% liquid resin. The blast furnace carbon grouting material has good fluidity and meets the construction requirements of the blast furnace grouting material. At the same time, after the grouting material is used to seal the cracks in the furnace cylinder, it has excellent strength performance at high temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of refractory materials, and in particular relates to a blast furnace carbonaceous grouting material and a preparation method thereof. Background Art

[0002] After a period of production, the carbon bricks in the hearth area of ​​the blast furnace will be damaged due to poor physical and chemical properties or thermal stress caused by the hearth structure, resulting in annular cracks. The annular cracks of the carbon bricks and the gas channel between the lining and the furnace shell or cooling equipment will cause the hot gas to flow in the through channel, which will increase the local temperature of the hearth area. On the other hand, the formation of "elephant's feet" will cause the carbon bricks in the hearth to become thinner, thereby affecting the outward movement of the 1150℃ isotherm in the hearth area and accelerating the erosion of the carbon bricks by the molten iron in the "dead iron layer". At this time, the blast furnace needs to be repaired. The main means of maintenance is to perform pressure grouting to seal the areas where the hearth temperature is too high. The pressure of the grouting material will fill and block the channel for gas leakage, thereby slowing down and solving the phenomenon of high hearth temperature.

[0003] Blast furnace grouting materials are mostly made of alumina and micropowder. For example, the Chinese patent document with publication number CN113481340A discloses a blast furnace grouting material for sealing the back of the cooling wall of the blast furnace body, which is made of alumina, silicon micropowder, curing agent, composite expansion agent, dispersant, and binder. The blast furnace grouting material has the characteristics of high strength, good fluidity, good sealing, and long life. Compared with other forms of refractory materials such as refractory bricks for blast furnace linings, grouting materials have higher requirements for material fluidity, because if the fluidity of the grouting material is not good, it cannot be effectively poured into the gap of the blast furnace to seal the cracks in the furnace. However, on the other hand, the improvement of the fluidity of the grouting material will inevitably lead to a decrease in strength, and carbonaceous grouting materials are usually difficult to sinter, and the strength of the caulking after it is poured cannot be effectively guaranteed. Summary of the invention

[0004] The technical problem solved by the present invention is to provide a blast furnace carbonaceous grouting material and a preparation method thereof. The blast furnace carbonaceous grouting material has good fluidity and meets the construction requirements of blast furnace grouting materials. At the same time, after the grouting material seals the cracks in the furnace cylinder, it has excellent strength performance at high temperature.

[0005] In order to solve the above problems, one aspect of the present invention provides a blast furnace carbon grouting material, the raw materials for preparing the blast furnace carbon grouting material include the following components in mass percentage:

[0006] Silicon carbide particles 10%~35%, petroleum coke particles 10%~32%, alumina particles 1%~5%, silicon carbide fine powder 30%~45%, coke powder 1%~8%, alumina powder 1%~4%, fused magnesia powder 1%~5%, silicon micropowder 1%~4%, quartz powder 2%~6%, metal aluminum powder 0.05%~1%, metal chromium powder 0.05%~1%, plus liquid resin 20%~30%.

[0007] Preferably, the raw materials for its preparation include the following components in percentage by mass:

[0008] Silicon carbide particles 16%~30%, petroleum coke particles 13%~26%, alumina particles 2%~3%, silicon carbide fine powder 36.9%~40.2%, coke powder 3%~5%, alumina powder 2%~2.5%, fused magnesia powder 3%~3.5%, silicon micropowder 2%~3%, quartz powder 3%~4%, metal aluminum powder 0.1%~0.5%, metal chromium powder 0.1%~0.8%, plus liquid resin 22%~28%.

[0009] Preferably, the raw materials for its preparation include the following components in percentage by mass:

[0010] Silicon carbide particles 20%~26%, petroleum coke particles 17%~22%, alumina particles 2%~3%, silicon carbide fine powder 36.9%~40.2%, coke powder 4%~5%, alumina powder 2%~2.5%, fused magnesia powder 3%~3.5%, silicon micropowder 2%~3%, quartz powder 3%~4%, metal aluminum powder 0.3%~0.5%, metal chromium powder 0.3%~0.6%, plus liquid resin 24%~26%.

[0011] Preferably, the mass ratio of metal aluminum powder, metal chromium powder and coke powder is 0.02~0.17:0.02~0.27:1.

[0012] Preferably, the mass ratio of alumina powder to fused magnesia powder is 0.6-0.8:1.

[0013] Preferably, the mass ratio of particles to fine powder in the preparation raw materials is 0.8-0.82:1.

[0014] Preferably, the particle size of silicon carbide particles is 1-0 mm; the particle size of petroleum coke particles is 1-0 mm; the particle size of alumina particles is 1-0 mm; the particle size of silicon carbide fine powder is 200 mesh; the particle size of coke powder is 200 mesh; and the particle size of alumina powder is 200 mesh.

[0015] Preferably, the particle size of the fused magnesia powder is 200 mesh; the particle size of the silicon powder is less than 5 μm; the particle size of the quartz powder is 325 mesh; the particle size of the metal aluminum powder is 325 mesh; and the particle size of the metal chromium powder is 325 mesh.

[0016] Preferably, in the alumina particles and alumina powder, Al2O3≥87wt%, Fe2O3≤1.5wt%, and the volume density of the alumina particles≥3.2g / cm 3 ;

[0017] In silicon carbide particles and silicon carbide fine powder, SiC ≥ 90wt%, Fe2O3 ≤ 2wt%;

[0018] In petroleum coke particles, ash content is less than 0.5%, volatile matter is less than 0.5%, and the true density of petroleum coke particles is greater than 2g / cm 3 .

[0019] The second aspect of the present invention provides a method for preparing the above-mentioned blast furnace carbonaceous grouting material, comprising:

[0020] The raw materials for preparing the carbonaceous grouting material for blast furnace are mixed to obtain the carbonaceous grouting material for blast furnace.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] The carbonaceous grouting material for blast furnace of the present invention adopts the combination of particles and micro powder to make the grouting material have suitable fluidity, so that the grouting material can be effectively poured into the gap of blast furnace during construction to seal the cracks of furnace; because the carbonaceous grouting material is difficult to sinter, when the resin binder is used, the grouting material begins to have strength at 100-200°C, but after 800°C, the carbon chain is burned off and loses the bonding ability, and the grouting material needs to have a certain fluidity, which will inevitably reduce its strength. In order to improve the strength of the grouting material at the working temperature after the seam is sealed, the present invention further adds fused magnesia powder to the raw material of the grouting material, which can form magnesium-aluminum tip with alumina at a high temperature of 1400°C The formation of spar and magnesium-aluminum spinel can effectively combine the raw materials of the grouting material together, improve the medium and high temperature strength, and make up for the shortcomings of the grouting material such as fine particle size, high porosity and low strength; and further added with metal aluminum powder and metal chromium powder, metal chromium powder can resist blast furnace gas erosion and enhance the matrix's acid corrosion resistance, and, as the blast furnace temperature continues to rise, metal aluminum powder, metal chromium powder, and coke powder react to form a Cr2AlC ternary layered ceramic structure. The formation of this ceramic structure can further effectively combine the raw materials in the grouting material together, thereby improving the high temperature strength. As the temperature continues to rise, carbon begins to graphitize, which further improves the strength of the grouting material. In the blast furnace carbonaceous grouting material, magnesium-aluminum spinel, Cr2AlC ternary layered ceramics, and graphitized carbon are formed within different temperature ranges, and the three cooperate with each other to improve the strength of the grouting material within the entire working temperature range; in addition, since the added metal aluminum powder and metal chromium powder are both metal powders, the metal powders have a large specific gravity and poor fluidity, the fluidity of the grouting material will be reduced. In order to compensate for the problem of poor fluidity caused by the addition of metal powders, the present invention further regulates the ratio of the raw materials for preparing the grouting material, and regulates the proportion of particles and fine powder in the raw materials, so as to improve the high-temperature strength of the grouting material while ensuring that it has good fluidity. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] One aspect of an embodiment of the present invention provides a blast furnace carbon grouting material, wherein the raw materials for preparing the blast furnace carbon grouting material include the following components in percentage by mass:

[0025] Silicon carbide particles 10%~35%, petroleum coke particles 10%~32%, alumina particles 1%~5%, silicon carbide fine powder 30%~45%, coke powder 1%~8%, alumina powder 1%~4%, fused magnesia powder 1%~5%, silicon micropowder 1%~4%, quartz powder 2%~6%, metal aluminum powder 0.05%~1%, metal chromium powder 0.05%~1%, plus liquid resin 20%~30%.

[0026] The carbonaceous grouting material for blast furnaces in the embodiment of the present invention adopts a combination of particles and micropowders to make the grouting material have suitable fluidity, so that the grouting material can be effectively poured into the gaps of the blast furnace during construction to seal the cracks in the furnace; since the carbonaceous grouting material is difficult to sinter, when a resin binder is used, the grouting material begins to have strength at 100-200°C, but after 800°C, the carbon chain is burned off and loses its binding ability, and the grouting material needs to have a certain fluidity, which will inevitably reduce its strength. In order to improve the strength of the grouting material at the working temperature after the seams are sealed, the present invention further adds fused magnesia powder to the raw materials of the grouting material, which can form magnesium with alumina at a high temperature of 1400°C. The formation of aluminum spinel and magnesium aluminum spinel can effectively combine the raw materials of the grouting material together, improve the medium and high temperature strength, and make up for the shortcomings of the grouting material such as fine particle size, high porosity and low strength; and further added with metal aluminum powder and metal chromium powder, metal chromium powder can resist blast furnace gas erosion and enhance the matrix's acid corrosion resistance. Moreover, as the blast furnace temperature continues to rise, metal aluminum powder, metal chromium powder and coke powder react to form a Cr2AlC ternary layered ceramic structure. The formation of this ceramic structure can further effectively combine the raw materials in the grouting material together, thereby improving the high temperature strength. As the temperature continues to rise, carbon begins to graphitize, which further improves the strength of the grouting material. In the blast furnace carbonaceous grouting material, magnesium-aluminum spinel, Cr2AlC ternary layered ceramics, and graphitized carbon are formed within different temperature ranges, and the three cooperate with each other to improve the strength of the grouting material within the entire working temperature range; in addition, since the added metal aluminum powder and metal chromium powder are both metal powders, the metal powders have a large specific gravity and poor fluidity, the fluidity of the grouting material will be reduced. In order to compensate for the problem of poor fluidity caused by the addition of metal powders, the present invention further regulates the ratio of the raw materials for preparing the grouting material, and regulates the proportion of particles and fine powder in the raw materials, so as to improve the high-temperature strength of the grouting material while ensuring that it has good fluidity.

[0027] In some embodiments, preferably, the raw materials for preparing the carbonaceous grouting material for blast furnace include the following components in percentage by mass:

[0028] Silicon carbide particles 16%~30%, petroleum coke particles 13%~26%, alumina particles 2%~3%, silicon carbide fine powder 36.9%~40.2%, coke powder 3%~5%, alumina powder 2%~2.5%, fused magnesia powder 3%~3.5%, silicon micropowder 2%~3%, quartz powder 3%~4%, metal aluminum powder 0.1%~0.5%, metal chromium powder 0.1%~0.8%, plus liquid resin 22%~28%. When the raw materials are composed of components in this mass percentage range, the blast furnace carbon grouting material has both better fluidity and better high temperature strength.

[0029] In some embodiments, the raw materials for preparing the carbonaceous grouting material for blast furnace include the following components in percentage by mass:

[0030] Silicon carbide particles 20%~26%, petroleum coke particles 17%~22%, alumina particles 2%~3%, silicon carbide fine powder 36.9%~40.2%, coke powder 4%~5%, alumina powder 2%~2.5%, fused magnesia powder 3%~3.5%, silicon micropowder 2%~3%, quartz powder 3%~4%, metal aluminum powder 0.3%~0.5%, metal chromium powder 0.3%~0.6%, plus liquid resin 24%~26%. When the raw materials are composed of components in this mass percentage range, the blast furnace carbon grouting material has both better fluidity and better high temperature strength.

[0031] In some embodiments, the metal aluminum powder, metal chromium powder, and coke powder can generate an appropriate amount of Cr2AlC ternary layered ceramics within a certain mass ratio range to improve the strength of the grouting material. In addition to reacting with the metal aluminum powder and metal chromium powder to generate Cr2AlC ternary layered ceramics, the coke powder is also used as a raw material for the grouting material. A large number of experimental studies have shown that, preferably, the mass ratio of metal aluminum powder, metal chromium powder, and coke powder is 0.02~0.17:0.02~0.27:1. Within this mass ratio range, an appropriate amount of Cr2AlC ternary layered ceramics can be generated, which effectively improves the high-temperature strength of the grouting material.

[0032] In some embodiments, the amount of magnesium-aluminum spinel generated by the reaction of alumina powder and fused magnesia powder should be appropriate. Excessive generation of magnesium-aluminum spinel will cause the grouting material to expand greatly, which will reduce its strength. In addition, alumina powder is also used as a raw material for grouting materials. A large number of experimental studies have shown that, preferably, the mass ratio of alumina powder to fused magnesia powder is 0.6 to 0.8: 1. Within this mass ratio range, an appropriate amount of magnesium-aluminum spinel can be generated, which effectively improves the medium and high temperature strength of the grouting material.

[0033] In some embodiments, the mass ratio of particles to fine powder in the raw materials for preparing blast furnace carbon grouting material is 0.8~0.82: 1. Due to the addition of metal aluminum powder and metal chromium powder, the overall specific gravity of the grouting material increases and the fluidity becomes worse. In order to take into account the fluidity and high temperature strength of the grouting material, the present invention further regulates the ratio of the raw materials for preparing the grouting material, and regulates the ratio of particles to fine powder in the raw materials, so that the high temperature strength of the grouting material is improved while ensuring that it has good fluidity.

[0034] In some embodiments, the silicon carbide particles have a particle size of 1-0 mm.

[0035] In some embodiments, the petroleum coke particles have a particle size of 1-0 mm.

[0036] In some embodiments, the alumina particles have a particle size of 1-0 mm.

[0037] In some embodiments, the particle size of the silicon carbide fine powder is 200 mesh.

[0038] In some embodiments, the particle size of the coke fines is 200 mesh.

[0039] In some embodiments, the alumina powder has a particle size of 200 mesh.

[0040] In some embodiments, the particle size of the fused magnesia powder is 200 mesh.

[0041] In some embodiments, the particle size of the silica powder is less than 5 μm.

[0042] In some embodiments, the quartz powder has a particle size of 325 mesh.

[0043] In some embodiments, the particle size of the metallic aluminum powder is 325 mesh.

[0044] In some embodiments, the particle size of the metallic chromium powder is 325 mesh.

[0045] In some embodiments, in the alumina particles and alumina powder, Al2O3≥87wt%, Fe2O3≤1.5wt%, and the volume density of the alumina particles≥3.2g / cm 3 .

[0046] In some embodiments, in the silicon carbide particles or silicon carbide fine powder, SiC ≥ 90 wt %, and Fe 2 O 3 ≤ 2 wt %.

[0047] In some embodiments, the ash content of the petroleum coke particles is less than 0.5%, the volatile matter is less than 0.5%, and the true density of the petroleum coke particles is greater than 2 g / cm 3 .

[0048] A second aspect of an embodiment of the present invention provides a method for preparing the above-mentioned blast furnace carbonaceous grouting material, comprising:

[0049] The raw materials for preparing the carbonaceous grouting material for blast furnace are mixed to obtain the carbonaceous grouting material for blast furnace.

[0050] In the following embodiments, in the alumina particles and alumina powder, Al2O3≥87wt%, Fe2O3≤1.5wt%, and the volume density of the alumina particles≥3.2g / cm 3 In silicon carbide particles and silicon carbide fine powder, SiC ≥ 90wt%, Fe2O3 ≤ 2wt%. In petroleum coke particles, ash content < 0.5%, volatile matter < 0.5%, true density of petroleum coke particles > 2g / cm 3 . Example 1

[0051] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0052] 10% silicon carbide particles with a particle size of 1-0mm, 31% petroleum coke particles with a particle size of 1-0mm, 1% alumina particles with a particle size of 200 mesh, 44% silicon carbide fine powder with a particle size of 200 mesh, 1% coke powder with a particle size of 200 mesh, 4% alumina powder with a particle size of 200 mesh, 1% fused magnesia powder with a particle size of 200 mesh, 1% silicon micropowder with a particle size less than 5μm, 6% quartz powder with a particle size of 325 mesh, 0.05% metal aluminum powder with a particle size of 325 mesh, 0.95% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0053] The preparation method of the carbonaceous grouting material for blast furnace of the present embodiment comprises: preparing the raw materials except the liquid resin according to the above proportion, mixing and stirring for 2 minutes, adding the liquid resin and stirring for another 3 minutes to obtain the carbonaceous grouting material for blast furnace. Example 2

[0054] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0055] 16% silicon carbide particles with a particle size of 1-0mm, 26% petroleum coke particles with a particle size of 1-0mm, 3% alumina particles with a particle size of 200 mesh, 37.7% silicon carbide fine powder with a particle size of 200 mesh, 3% coke powder with a particle size of 200 mesh, 2.5% alumina powder with a particle size of 200 mesh, 3.5% fused magnesia powder with a particle size of 200 mesh, 3% silicon micropowder with a particle size less than 5μm, 4% quartz powder with a particle size of 325 mesh, 0.5% metal aluminum powder with a particle size of 325 mesh, 0.8% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0056] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Example 3

[0057] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0058] 18% silicon carbide particles with a particle size of 1-0mm, 24% petroleum coke particles with a particle size of 1-0mm, 3% alumina particles with a particle size of 200 mesh, 37.8% silicon carbide fine powder with a particle size of 200 mesh, 3% coke powder with a particle size of 200 mesh, 2.5% alumina powder with a particle size of 200 mesh, 3.5% fused magnesia powder with a particle size of 200 mesh, 3% silicon micropowder with a particle size less than 5μm, 4% quartz powder with a particle size of 325 mesh, 0.5% metal aluminum powder with a particle size of 325 mesh, 0.7% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0059] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Example 4

[0060] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0061] 20% silicon carbide particles with a particle size of 1-0mm, 22% petroleum coke particles with a particle size of 1-0mm, 3% alumina particles with a particle size of 200 mesh, 36.9% silicon carbide fine powder with a particle size of 200 mesh, 4% coke powder with a particle size of 200 mesh, 2.5% alumina powder with a particle size of 200 mesh, 3.5% fused magnesia powder with a particle size of 200 mesh, 3% silicon micropowder with a particle size less than 5μm, 4% quartz powder with a particle size of 325 mesh, 0.5% metal aluminum powder with a particle size of 325 mesh, 0.6% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0062] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Example 5

[0063] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0064] 22% silicon carbide particles with a particle size of 1-0mm, 21% petroleum coke particles with a particle size of 1-0mm, 2% alumina particles with a particle size of 200 mesh, 40.1% silicon carbide fine powder with a particle size of 200 mesh, 4% coke powder with a particle size of 200 mesh, 2% alumina powder with a particle size of 200 mesh, 3% fused magnesia powder with a particle size of 200 mesh, 2% silicon micropowder with a particle size less than 5μm, 3% quartz powder with a particle size of 325 mesh, 0.4% metal aluminum powder with a particle size of 325 mesh, 0.5% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0065] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Example 6

[0066] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0067] 24% silicon carbide particles with a particle size of 1-0mm, 19% petroleum coke particles with a particle size of 1-0mm, 2% alumina particles with a particle size of 200 mesh, 40.2% silicon carbide fine powder with a particle size of 200 mesh, 4% coke powder with a particle size of 200 mesh, 2% alumina powder with a particle size of 200 mesh, 3% fused magnesia powder with a particle size of 200 mesh, 2% silicon micropowder with a particle size less than 5μm, 3% quartz powder with a particle size of 325 mesh, 0.4% metal aluminum powder with a particle size of 325 mesh, 0.4% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0068] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Example 7

[0069] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0070] 26% silicon carbide particles with a particle size of 1-0mm, 17% petroleum coke particles with a particle size of 1-0mm, 2% alumina particles with a particle size of 200 mesh, 39.4% silicon carbide fine powder with a particle size of 200 mesh, 5% coke powder with a particle size of 200 mesh, 2% alumina powder with a particle size of 200 mesh, 3% fused magnesia powder with a particle size of 200 mesh, 2% silicon micropowder with a particle size less than 5μm, 3% quartz powder with a particle size of 325 mesh, 0.3% metal aluminum powder with a particle size of 325 mesh, 0.3% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0071] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Example 8

[0072] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0073] 28% silicon carbide particles with a particle size of 1-0mm, 15% petroleum coke particles with a particle size of 1-0mm, 2% alumina particles with a particle size of 200 mesh, 39.6% silicon carbide fine powder with a particle size of 200 mesh, 5% coke powder with a particle size of 200 mesh, 2% alumina powder with a particle size of 200 mesh, 3% fused magnesia powder with a particle size of 200 mesh, 2% silicon micropowder with a particle size less than 5μm, 3% quartz powder with a particle size of 325 mesh, 0.2% metal aluminum powder with a particle size of 325 mesh, 0.2% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0074] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Example 9

[0075] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0076] 30% silicon carbide particles with a particle size of 1-0mm, 13% petroleum coke particles with a particle size of 1-0mm, 2% alumina particles with a particle size of 200 mesh, 39.8% silicon carbide fine powder with a particle size of 200 mesh, 5% coke powder with a particle size of 200 mesh, 2% alumina powder with a particle size of 200 mesh, 3% fused magnesia powder with a particle size of 200 mesh, 2% silicon micropowder with a particle size less than 5μm, 3% quartz powder with a particle size of 325 mesh, 0.1% metal aluminum powder with a particle size of 325 mesh, 0.1% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0077] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Example 10

[0078] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0079] 34% silicon carbide particles with a particle size of 1-0mm, 10% petroleum coke particles with a particle size of 1-0mm, 5% alumina particles with a particle size of 200 mesh, 30% silicon carbide fine powder with a particle size of 200 mesh, 8% coke powder with a particle size of 200 mesh, 1% alumina powder with a particle size of 200 mesh, 5% fused magnesia powder with a particle size of 200 mesh, 4% silicon micropowder with a particle size less than 5μm, 2% quartz powder with a particle size of 325 mesh, 0.95% metal aluminum powder with a particle size of 325 mesh, 0.05% metal chromium powder with a particle size of 325 mesh, and 25% liquid resin.

[0080] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Embodiment 11

[0081] The remaining components and contents of the raw materials for preparing the carbon grouting material for blast furnace described in this embodiment are the same as those in Example 6, except that the coke powder is 3.7%, the metal aluminum powder is 0.1%, and the metal chromium powder is 1%. That is, the mass ratio of the metal aluminum powder, the metal chromium powder, and the coke powder is 0.027:0.27:1. The preparation method of the carbon grouting material for blast furnace in this embodiment is the same as that in Example 1. Example 12

[0082] The remaining components and contents of the raw materials for preparing the carbon grouting material for blast furnace described in this embodiment are the same as those in Example 6, except that the coke powder is 4%, the metal aluminum powder is 0.68%, and the metal chromium powder is 0.12%. That is, the mass ratio of the metal aluminum powder, the metal chromium powder, and the coke powder is 0.17:0.03:1. The preparation method of the carbon grouting material for blast furnace in this embodiment is the same as that in Example 1. Example 13

[0083] The remaining components and contents of the raw materials for preparing the carbon grouting material for blast furnace described in this embodiment are the same as those in Example 6, except that the coke powder is 3.7%, the metal aluminum powder is 0.05%, and the metal chromium powder is 1.05%. That is, the mass ratio of the metal aluminum powder, the metal chromium powder, and the coke powder is 0.014:0.284:1. The preparation method of the carbon grouting material for blast furnace in this embodiment is the same as that in Example 1. Embodiment 14

[0084] The remaining components and contents of the raw materials for preparing the carbon grouting material for blast furnace described in this embodiment are the same as those in Example 6, except that the coke powder is 4%, the metal aluminum powder is 0.75%, and the metal chromium powder is 0.05%. That is, the mass ratio of the metal aluminum powder, the metal chromium powder, and the coke powder is 0.188:0.013:1. The preparation method of the carbon grouting material for blast furnace in this embodiment is the same as that in Example 1. Embodiment 15

[0085] The remaining components and contents of the raw materials for preparing the carbon grouting material for blast furnace described in this embodiment are the same as those in Example 6, except that the alumina powder is 1.9% and the fused magnesia powder is 3.1%. That is, the mass ratio of the alumina powder to the fused magnesia powder is 0.61:1. The preparation method of the carbon grouting material for blast furnace in this embodiment is the same as that in Example 1. Example 16

[0086] The remaining components and contents of the raw materials for preparing the carbon grouting material for blast furnace described in this embodiment are the same as those in Example 6, except that the alumina powder is 2.2% and the fused magnesia powder is 2.8%. That is, the mass ratio of the alumina powder to the fused magnesia powder is 0.79:1. The preparation method of the carbon grouting material for blast furnace in this embodiment is the same as that in Example 1. Embodiment 17

[0087] The remaining components and contents of the raw materials for preparing the carbon grouting material for blast furnace described in this embodiment are the same as those in Example 6, except that the alumina powder is 1.7% and the fused magnesia powder is 3.3%. That is, the mass ratio of the alumina powder to the fused magnesia powder is 0.52:1. The preparation method of the carbon grouting material for blast furnace in this embodiment is the same as that in Example 1. Embodiment 18

[0088] The remaining components and contents of the raw materials for preparing the carbon grouting material for blast furnace described in this embodiment are the same as those in Example 6, except that the alumina powder is 2.4% and the fused magnesia powder is 2.6%. That is, the mass ratio of the alumina powder to the fused magnesia powder is 0.92:1. The preparation method of the carbon grouting material for blast furnace in this embodiment is the same as that in Example 1. Embodiment 19

[0089] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0090] 24% of silicon carbide particles with a particle size of 1-0mm, 24% of petroleum coke particles with a particle size of 1-0mm, 2% of alumina particles with a particle size of 200 mesh, 37.2% of silicon carbide fine powder with a particle size of 200 mesh, 4% of coke powder with a particle size of 200 mesh, 2% of alumina powder with a particle size of 200 mesh, 3% of fused magnesia powder with a particle size of 200 mesh, 1% of silicon micropowder with a particle size of less than 5μm, 2% of quartz powder with a particle size of 325 mesh, 0.4% of metal aluminum powder with a particle size of 325 mesh, 0.4% of metal chromium powder with a particle size of 325 mesh, and 25% of liquid resin. That is, the mass ratio of particles to fine powder in the raw materials is 1:1.

[0091] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Embodiment 20

[0092] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0093] 24% of silicon carbide particles with a particle size of 1-0mm, 30% of petroleum coke particles with a particle size of 1-0mm, 2% of alumina particles with a particle size of 200 mesh, 30.2% of silicon carbide fine powder with a particle size of 200 mesh, 4% of coke powder with a particle size of 200 mesh, 2% of alumina powder with a particle size of 200 mesh, 3% of fused magnesia powder with a particle size of 200 mesh, 2% of silicon micropowder with a particle size of less than 5μm, 2% of quartz powder with a particle size of 325 mesh, 0.4% of metal aluminum powder with a particle size of 325 mesh, 0.4% of metal chromium powder with a particle size of 325 mesh, and 25% of liquid resin. That is, the mass ratio of particles to fine powder in the raw materials is 1.27:1.

[0094] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1. Embodiment 21

[0095] The carbonaceous grouting material for blast furnace described in this embodiment comprises the following components in percentage by mass:

[0096] 24% of silicon carbide particles with a particle size of 1-0mm, 15% of petroleum coke particles with a particle size of 1-0mm, 2% of alumina particles with a particle size of 200 mesh, 42.2% of silicon carbide fine powder with a particle size of 200 mesh, 4% of coke powder with a particle size of 200 mesh, 2% of alumina powder with a particle size of 200 mesh, 3% of fused magnesia powder with a particle size of 200 mesh, 3% of silicon micropowder with a particle size of less than 5μm, 4% of quartz powder with a particle size of 325 mesh, 0.4% of metal aluminum powder with a particle size of 325 mesh, 0.4% of metal chromium powder with a particle size of 325 mesh, and 25% of liquid resin. That is, the mass ratio of particles to fine powder in the raw materials is 0.7:1.

[0097] The preparation method of the blast furnace carbonaceous grouting material in this embodiment is the same as that in Example 1.

[0098] Comparative Example 1

[0099] The remaining components and relative proportions of the raw materials for preparing the blast furnace carbon grouting material in this comparative example are the same as those in Example 6, except that no metal aluminum powder and metal chromium powder are added.

[0100] The fluidity of the above-mentioned embodiments and comparative examples was measured. The fluidity measurement method was determined according to the self-flow method in 5.4 of Part 4 of GB / T 4513.4-2017 Unshaped Refractory Materials, Determination of Castable Fluidity. The high-temperature strength performance of the blast furnace carbon grouting materials of the above-mentioned embodiments and comparative examples was measured. Specifically: according to the ratio selected in the above-mentioned embodiments and comparative examples, the raw material mixture was first stirred for 2 minutes, and then stirred for 3 minutes after adding the liquid resin, and vibrated and cast into a sample block of 40mm×40mm×160mm, cured for 24 hours, baked at 110℃×24h, fired in a high-temperature furnace at 1350℃×3h, and tested for hot flexural strength at 1400℃×0.5h. The measurement results are shown in Table 1 below.

[0101] It can be seen from the data in Table 1 that the carbon grouting material for blast furnace in the comparative example has better fluidity, but poor compressive strength and high temperature flexural strength. In contrast, the carbon grouting material for blast furnace in each embodiment of the present invention greatly improves compressive strength and high temperature flexural strength while ensuring good fluidity.

[0102] In each embodiment of the present invention, in Embodiments 1-10, the mass percentages of each component of the raw materials are different, among which, compared with Embodiments 1 and 10, the mass percentages of each component in Embodiments 2-9 are in a preferred range, and the fluidity, compressive strength, and high-temperature flexural strength of the blast furnace carbon grouting material are better; further, compared with Embodiments 2, 3, 8, and 9, the fluidity, compressive strength, and high-temperature flexural strength of the blast furnace carbon grouting material in Embodiments 4-7 are better, and the mass percentages of each component are in a further preferred range.

[0103] Compared with Example 6, Examples 11-14 differ in that the mass contents of coke powder, metal aluminum powder and metal chromium powder added are different. Among them, the mass ratio of coke powder, metal aluminum powder and metal chromium powder in Examples 6, 11 and 12 is better, and the obtained blast furnace carbon grouting material has better fluidity, compressive strength and high temperature flexural strength.

[0104] Compared with Example 6, Examples 15-18 differ in that the mass content of the added alumina powder and fused magnesia powder is different. Among them, the mass ratio of alumina powder and fused magnesia powder in Examples 6, 15, and 16 is better, and the obtained blast furnace carbon grouting material has better fluidity, compressive strength, and high-temperature flexural strength.

[0105] Compared with Example 6, Examples 19-21 differ in that the mass ratio of particles to fine powder in the raw materials is different. Among them, the mass ratio of particles to fine powder in the raw materials of Examples 6 and 19 is more optimal, and the obtained blast furnace carbon grouting material has better fluidity, compressive strength, and high-temperature flexural strength.

[0106] Table 1

[0107]

[0108] Obviously, the above embodiments are merely examples for the purpose of clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived therefrom are still within the scope of protection of the invention.

Claims

1. A blast furnace carbon grouting material, characterized in that: The raw materials for its preparation include the following components in percentage by mass: Silicon carbide particles 16%~30%, petroleum coke particles 13%~26%, alumina particles 2%~3%, silicon carbide fine powder 36.9%~40.2%, coke powder 3%~5%, alumina powder 2%~2.5%, fused magnesia powder 3%~3.5%, silicon micropowder 2%~3%, quartz powder 3%~4%, metal aluminum powder 0.1%~0.5%, metal chromium powder 0.1%~0.8%, plus liquid resin 22%~28%; the mass ratio of metal aluminum powder, metal chromium powder and coke powder is 0.02~0.17:0.02~0.27:1; the mass ratio of particles to fine powder in its preparation raw materials is 0.8~1:

1.

2. The carbonaceous grouting material for blast furnace according to claim 1, characterized in that: The raw materials for its preparation include the following components in percentage by mass: Silicon carbide particles 20%~26%, petroleum coke particles 17%~22%, alumina particles 2%~3%, silicon carbide fine powder 36.9%~40.2%, coke powder 4%~5%, alumina powder 2%~2.5%, fused magnesia powder 3%~3.5%, silicon micropowder 2%~3%, quartz powder 3%~4%, metal aluminum powder 0.3%~0.5%, metal chromium powder 0.3%~0.6%, plus liquid resin 24%~26%.

3. The carbonaceous grouting material for blast furnace according to claim 1, characterized in that: The mass ratio of alumina powder to fused magnesia powder is 0.6~0.8:

1.

4. The carbonaceous grouting material for blast furnace according to claim 1, characterized in that: The particle size of silicon carbide particles is 1-0mm; The particle size of petroleum coke particles is 1-0mm; The particle size of alumina particles is 1-0mm; The particle size of silicon carbide fine powder is 200 mesh; The particle size of coke powder is 200 mesh; The particle size of alumina powder is 200 mesh.

5. The carbonaceous grouting material for blast furnace according to claim 1, characterized in that: The particle size of fused magnesia powder is 200 mesh; The particle size of silicon powder is less than 5μm; The particle size of quartz powder is 325 mesh; The particle size of the aluminum powder is 325 mesh; The particle size of the metallic chromium powder is 325 mesh.

6. The carbonaceous grouting material for blast furnace according to claim 1, characterized in that: In alumina particles and alumina powder, Al2O3≥87wt%, Fe2O3≤1.5wt%, and the volume density of alumina particles≥3.2g / cm 3 ; In silicon carbide particles and silicon carbide fine powder, SiC ≥ 90wt%, Fe2O3 ≤ 2wt%; In petroleum coke particles, ash content is less than 0.5%, volatile matter is less than 0.5%, and the true density of petroleum coke particles is greater than 2g / cm 3 .

7. A method for preparing a blast furnace carbon grouting material according to any one of claims 1 to 6, characterized in that: include: The raw materials for preparing the carbonaceous grouting material for blast furnace are mixed to obtain the carbonaceous grouting material for blast furnace.

Citation Information

Patent Citations

  • Blast furnace grouting material used for sealing back of cooling wall of blast furnace body

    CN113481340A

  • Anhydrous stemming for large and medium sized blast furnace and preparation method of anhydrous stemming

    CN106699206A

  • Magnesium-chromium silicon carbide refractory material and preparation method thereof

    CN107244903A

  • Magnesia carbon brick toughened by high-temperature liquid phase and preparation method thereof

    CN115321956A